British colonial expansion through the Indian diaspora: the pattern of Indian overseas migration - Shan, Tang; Haitao, Jia (Cappadocia Journal of Area Studies, 2020)
Historically, India played a crucial role in the establishment and maintenance of the British Empire overseas. Through the conquest of India, the British not only acquired great material wealth and secured the accumulation of industrial capital, but also obtained a sizeable pool of skilled human resources to facilitate its colonial expansion. At present, the total number of overseas Indians has exceeded 30 million, making up the second largest Diaspora after that of China. This massive immigrant group and its overseas distribution were inseparable from the British conquest of India and its borrowing and export of human resources to India. Through conscription, the recruitment of service personnel, the exile of criminals and the utilization of indentured labor, the British colonial rulers transferred Indian manpower to other colonies to serve their colonialist interests. This expansion was also accompanied by the movement of a large number of Indian businessmen, and all these Indian immigrants would lay the basic foundation and structure of today's global Indian Diaspora.